Implementasi Pendidikan Nonformal Program Auntansi Di Wilayah Jakarta Timur - Tri Hartadi, Galih; Fitriana Sitorus, Onny (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
Education is a conscious and planned effort to create a learning atmosphere that allows students to have spiritual potential, self-control, personality, develop intelligence, noble character and skills. Education cannot be separated from humans and plays an important role in developing individual intelligence and abilities so that their development runs well.  Non-formal education programs have the same important position as formal education in development. According to Law Number 20 of 2003, the management of non-formal education in Indonesia is also in the spotlight because there are still problems occurring in the field, such as lack of coordination, scarcity of professional educators, and low learning motivation. The purpose of this research is to find out how planning, organizing and evaluating institutions carry out accounting programs. The research method uses qualitative methods. The research subject is addressed to participants, instructors and managers. The research results show that management is carried out well, this refers to planning, organizing and evaluating well.